NDMA formation by chloramination of ranitidine: Kinetics and mechanism - Roux, J.; Gallard, H.; Croué, Jean-Philippe; Papot, S.; Deborde, M. (American Chemical Society, 2012)
The kinetics of decomposition of the pharmaceutical ranitidine (a major precursor of NDMA) during chloramination was investigated and some decomposition byproducts were identified by using high performance liquid chromatography coupled with mass spectrometry (HPLC-MS). The reaction between monochloramine and ranitidine followed second order kinetics and was acid-catalyzed. Decomposition of ranitidine formed different byproducts depending on the applied monochloramine concentration. Most identified products were chlorinated and hydroxylated analogues of ranitidine. In excess of monochloramine, nucleophilic substitution between ranitidine and monochloramine led to byproducts that are critical intermediates involved in the formation of NDMA, for example, a carbocation formed from the decomposition of the methylfuran moiety of ranitidine. A complete mechanism is proposed to explain the high formation yield of NDMA from chloramination of ranitidine. These results are of great importance to understand the formation of NDMA by chloramination of tertiary amines.